Prevalence of Ehrlichia canis infection in thrombocytopenic dogs from Rio de Janeiro, Brazil - Macieira, Daniel de Barros (Veterinary clinical pathology, 2005)
BACKGROUND: Infection with Ehrlichia canis causes a highly variable, multisystemic disease in dogs. Nevertheless, many clinicians in Rio de Janeiro, Brazil, use the presence of only thrombocytopenia to make a presumptive diagnosis of E canis infection